2013
DOI: 10.1002/ijc.28280
|View full text |Cite|
|
Sign up to set email alerts
|

HtrA1 in human urothelial bladder cancer: A secreted protein and a potential novel biomarker

Abstract: Our aim was to analyze the expression of the serine protease HtrA1 in human bladder tissue and urine in order to point out its possible association with the presence of urothelial bladder cancer. Bladder tissue and urine specimens from cancer patients with different tumor grades and stages (n 5 68) and from individuals with cystitis (n 5 16) were collected along with biopsy specimens and urine from healthy individuals (n 5 68). For the first time, we demonstrated by immunohistochemistry that HtrA1 protein is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…S5D). This is consistent with previous studies that have shown the 38 kDa band is an autocatalytic product of the full length 50 kDa HtrA1 protein (28). Overall, SK-N-SH secreted HtrA1 protein levels were increased by 2.1-fold (p = 0.0002) after 9 days in culture with ATRA (Suppl.…”
Section: Introductionsupporting
confidence: 92%
“…S5D). This is consistent with previous studies that have shown the 38 kDa band is an autocatalytic product of the full length 50 kDa HtrA1 protein (28). Overall, SK-N-SH secreted HtrA1 protein levels were increased by 2.1-fold (p = 0.0002) after 9 days in culture with ATRA (Suppl.…”
Section: Introductionsupporting
confidence: 92%
“…Therefore they proposed that the N-terminal domain may function as a redox-sensing element that regulates autoproteolytic activity of HtrA1 in vivo depending on the cellular redox state [114]. Their conclusion is closely connected to the earlier findings showing that HtrA1 undergoes a limited proteolytic processing [24,115,116]. Chien et al [24] demonstrated that in response to paclitaxel treatment of ovarian cancer cells HtrA1 underwent autocatalytic cleavage resulting in generation of the protease variant lacking the N-terminal domain.…”
Section: Structural Features Of Htra1mentioning
confidence: 71%
“…Although both the full-length HtrA1 and the processed form of the enzyme showed a similar proteolytic activity in vitro, the latter was more active in inducing apoptotic cell death [24]. The processed form of HtrA1 was observed in ovarian cell lines following anoikis-inducing conditions [15] and also in tumor tissues from patients with urothelial bladder cancer [116]. Apart from proving that redox changes influence HtrA1 cleavage in a cell, there still remains an open question, how HtrA1 lacking its N-terminal domain is regulated in vivo.…”
Section: Structural Features Of Htra1mentioning
confidence: 94%
“…17,36 Recently, reduced levels of the autolytic ∼38 kDa product of HtrA1 were found to correlate with neoplastic bladder tissue undergoing cancerous transformation, which indeed highlights the importance of understanding the functional maturation of HtrA1 and the potential prognostic value of the autolytic forms. 28 …”
Section: Discussionmentioning
confidence: 99%
“…20,21 The specific downregulation of HtrA1 in the latter case promotes the sustained survival of cancer cells and the development of malignant metastatic behavior, 20,22,23 most likely correlated with the intracellular HtrA1 associated with microtubules and affecting cell migratory and signaling properties. 3,14,2427 Interestingly, autolytically N-terminally truncated forms of HtrA1 exist in vivo , and such forms have been suggested as prognostic markers in urothelial bladder cancer 28 and in preeclamptic pregnancies. 18 The exact role and trigger of autolytic maturation is at present unknown.…”
mentioning
confidence: 99%